Neurogenic chronic idiopathic intestinal pseudo-obstruction, patent ductus arteriosus, and thrombocytopenia segregating as an X linked recessive disorder. Issue 8 (August 1997) - FitzPatrick, D R; Strain, L; Thomas, A E; Barr, D G; Todd, A; Smith, N M; Scobie, W G
Abstract : We present a family with three affected males in two generations with congenital neurogenic chronic idiopathic intestinal pseudo-obstruction (CIIP), patent ductus arteriosus, and large platelet thrombocytopenia apparently segregating as an X linked recessive disorder. The pattern of segregation of DNA markers within the family is consistent with linkage to the previously described neurogenic CIIP (CIIPX) locus at Xq28. This combination may represent a new contiguous gene disorder and appears to have a good prognosis with supportive therapy.